Survival after Resection of Perihilar Cholangiocarcinoma in Patients with Lymph Node Metastases - Buettner, Stefan (HPB (Oxford), 2017)
INTRODUCTION: The aim of this study was to compare patients with PHC with lymph node metastases (LN+) who underwent a resection with patients who did not undergo resection because of locally advanced disease at exploratory laparotomy. METHODS: Consecutive LN+ patients who underwent a resection for PHC in 12 centers were compared with patients who did not undergo resection because of locally advanced disease at exploratory laparotomy in 2 centers. RESULTS: In the resected cohort of 119 patients, the median overall survival (OS) was 19 months and the estimated 1-, 3- and 5-year OS was 69%, 27% and 13%, respectively. In the non-resected cohort of 113 patients, median OS was 12 months and the estimated 1-, 3- and 5-year OS was 49%, 7%, and 3%, respectively. OS was better in the resected LN+ cohort (p<0.001). Positive resection margin (hazard ratio [HR]:1.54; 95%CI:0.97-2.45) and lymphovascular invasion (LVI) (HR:1.71; 95%CI:1.09-2.69) were independent poor prognostic factors in the resected cohort. CONCLUSION: Patients with PHC who underwent a resection for LN+ disease had better OS than patients who did not undergo resection because of locally advanced disease at exploratory laparotomy. LN+ PHC does not preclude 5-year survival after resection.